Non-Compliance with Hand Hygiene Standards among Nurses in Windhoek, Namibia - Chauke, Motshedisi E.; Mugweni, Rabecca (Africa Journal of Nursing and Midwifery, 2021)
Compliance with hand hygiene standards remains a challenge to many healthcare workers even though there is adequate scientific evidence supporting its role in improving health provider and patient safety, reducing costs and creating a positive working environment. This article describes factors that contribute to non-compliance with hand hygiene standards among nurses in Windhoek, Namibia. A non-experimental, quantitative descriptive and cross-sectional design was utilised. The target population consisted of nurses working at one state-owned hospital in Windhoek. A probability, stratified random sampling method was used to select a representative sample of 170 nurses from three categories of nurses, namely registered nurses, enrolled nurses and auxiliary nurses. A self-administered questionnaire was used to collect data, which were analysed by using SPSS version 23.0. According to the results, there were more institutional than personal factors that contribute to non-compliance with hand hygiene standards among the nurses. Institutional factors included inadequate resources for hand hygiene, the absence of role models such as colleagues and supervisors, workshops, seminars and continuing educational courses on hand hygiene as well as the absence of incentives or encouragement for compliers and sanctions against non-compliers with hand hygiene standards. The key recommendations included organisational commitment to hand hygiene, the creation of an organisational climate and culture that support hand hygiene, supervision and monitoring of hand hygiene, the supply of hand hygiene agents that do not cause skin dryness, and in-service education that focuses on hand hygiene.